PERBANDINGAN KEEFEKTIFAN MODEL TPS STAD PADA PEMBELAJARAN MATEMATIKA KELAS VI SEKOLAH DASAR NEGERI DI KABUPATEN SOPPENG - Andi Kaharuddin; Irma Magfirah (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2018)
This study aims to describe: (1) the effectiveness of Think Pair Share models in learning, (2) the effectiveness of Student Team Achievement Divisions models in learning, and (3) the comparisonof Think Pair Share and Student Team Achievement Divisions models effectiveness on mathematics learning in the sixth-grade students of public elementary schools in Soppeng Regency. This research is a quasi-experimental research. The population in this study was all sixth-grade students of public elementary schools in Soppeng Regency and the samples were determined by cluster stratified random sampling technique. The data collected comprises student learning outcomes data, students’ activity data in learning, and students’ response data on learning media. Students’ activity data and students’ responses were analyzed using descriptive analysis while students’ learning outcomes data were analyzed using descriptive statistical analysis and inferential statistics. The results of the t-test with a significant level 5 = 0.05 in the major hypothesis (1) the implementation of the effective Think Pair Share models, (2) the application of the Student Team Achievement Divisions model, and the major (3) for (a) student learning outcomes (posttest, gain) (b) students’ activity in learning (c) student response, shows that the application of Think Pair Share models is more effective than Student Team Achievement Divisions in the mathematics learning of the sixth-grade students of Public Elementary Schools in Soppeng District.